An Ambiguous Hermeneutic: Doubleness in Ingmar Bergman’s Quest for Self - Aziz, Ingy (AUC Knowledge Fountain, 2023)
One of the functions of art in all its forms is to provide the means for self-exploration and, in this way, to enable us to relate cultural representation to the question of meaning. The beauty of cinematic art is that it gives voice to our deepest and most profound concerns and enables us to bridge the gap between personal psychology and public understanding. As interpreters, we do not always unearth the answers that we seek, but we certainly gain more insight through delving into the minds of major filmmakers in the canon of modern cinema. This thesis is on the Swedish director, Ingmar Bergman, and how he integrated aspects of his life into his films in order to communicate with his audience and to plumb the depths of his own psyche as well. The quality of in-betweenness or doubleness that is present in Bergman’s films almost always propels the viewer to experience them in a state that resembles lucid dreaming. Bergman can be said to position his audience in a state of consciousness between slumber and wakefulness where we search for purpose and sometimes, but not always, find answers. In this context, I will also briefly visit three additional directors—Alejandro Jodorowsky, Andrei Tarkovsky, and Jean-Luc Godard—in terms of how their artistry enabled them to approach the problem of the self in comparable ways.